Mortgage in international private law - Widło, Jacek (Review of European and Comparative Law, 2019)
The article discusses the law applicable to the determination of a right secured on a property – i.e. a mortgage. Major reflections are preceded by the legal analysis of a mortgage, the concept of the Eurohypothec and the European Land Information Service – EULIS. What follows is a short review of mortgage regulations in selected legal systems (e.g. the French and German systems). The core of the article focuses on the rules for the search of the law applicable to a mortgage and their scope. The change of law for mortgages (properties), e.g. as a result of the change of borders, including a hostile incorporation (annexation), is also discussed.